2020
DOI: 10.1007/s11818-020-00280-7
|View full text |Cite
|
Sign up to set email alerts
|

Online cognitive behavioral group therapy (iCBT-I) for insomnia for school children and their parents

Abstract: Background Due to the SARS-CoV‑2 crisis, online adaptation of sleep trainings is necessary. As sleep disturbances in school children are common, prevention of chronification is essential. The aim of this study was to adapt an established age-oriented cognitive behavioral therapy for insomnia (CBT-I) group training for 5–10-year-old children with insomnia and their parents to an online version (group iCBT-I). Methods The adaptation procedure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Concerning the training application, in contrast to a previous study addressing children, our study had no personal contact [ 22 ] and no meeting each other in person [ 20 ]. However, some of the participants recommended the possibility of additive personal contacts for questions or further information (e.g., concerning specific sleep-related questions of asthma patients).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the training application, in contrast to a previous study addressing children, our study had no personal contact [ 22 ] and no meeting each other in person [ 20 ]. However, some of the participants recommended the possibility of additive personal contacts for questions or further information (e.g., concerning specific sleep-related questions of asthma patients).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-nine described disturbed sleep in the context of psychosocial and neuropsychiatric symptoms. As to specific management of sleep dysfunction during COVID-19, five studies of cognitive behavioral therapy (CBT) were available – two controlled trials of insomnia [ 11 , 12 ], one focused on worry and secondary insomnia [ 13 ], one case study [ 14 ] and a small online study in children [ 15 ]. Four similar treatment trials have begun or been proposed (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“… 5-10 y/o children with insomnia during COVID-19 6 children + parents Telehealth, online sessions of 3 h with parent; video session with child 67% of children showed reduced sleep problems according to parental rating. [ 15 ] Proposed Studies Elder et al. Public DSM-5 Insomniac vs. Good Sleepers Self-help leaflet for worry; stimulus control Await results; follow up at Day 7, 30 and 90 [ 31 ] Weiner et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the total test subjects, ∼37% of people had moderate to severe insomnia. Similarly, Schlarb et.al [ 72 ] conducted a study on children of age 5-10 years old along with their parents. The study found that 67% of children showed reduced sleep patterns during COVID-19.…”
Section: Covid-19 and Sleepmentioning
confidence: 99%